Creatures of the mangrove (Pittsburg : National Geographic Society, 1986)
Journey to the tiny island of Siarau on the northwest coast of Borneo, where a tidal mangrove forest survives. Caught between land and sea, the forest and its creatures have adapted in bizarre ways to the daily flooding of their habitat.
APD 2487